Digital skills and profile of each generation: a review - Elisa Cirilli; Paola Nicolini (INFAD, 2019)
The technological development is changing, involving and conditioning everyday life, making it faster, hyper-connected and immediate. New technologies can have a double outcome: positive, given that they take on the role of facilitator, or negative, when people tend to make excessive and unconscious use of it or technology repeatedly replaces human beings. Today, therefore, new skills are needed for the entire population, the digital skills, both in everyday life and in the labour market. These are transversal skills that allow human beings to choose the right technologies: to research, analyze data and choose reliable information from those that require further study, to check and verify the health of people, to interact with different and distant subjects in the world, to improve school learning, ... The plurality of people that this technological development is involving allows us to analyze the population in terms of generations, from Silent Generation to Alpha Generation. In this article we want to present a literature review within the Google Scholar database in the last 10 years using the terms digital skills and different generation. This preliminary research allows us to analyze the different theories that make for the Digital Skills a definition, dimensions and evaluation model, and the generational profiles in order to have a shared and common theory among the different professionals. Having an accurate background of digital skills and generational profiles favours the inclusion of all people, and the improvement of the quality of life in the creation of psycho-pedagogical projects and in the design of technological products.